2017
DOI: 10.1159/000479995
|View full text |Cite
|
Sign up to set email alerts
|

Mir-21 Promotes Cardiac Fibrosis After Myocardial Infarction Via Targeting Smad7

Abstract: Background/Aims: Cardiac fibrosis after myocardial infarction (MI) has been identified as an important factor in the deterioration of heart function. Previous studies have demonstrated that miR-21 plays an important role in various pathophysiological processes in the heart. However, the role of miR-21 in fibrosis regulation after MI remains unclear. Methods: To induce cardiac infarction, the left anterior descending coronary artery was permanently ligated of mice. First, we explored the expression of miR-21 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 45 publications
7
140
1
1
Order By: Relevance
“…Cao et al reported that tumour suppressor cell adhesion molecule 1 (CADM1) is the potential target of miR‐21 and miR‐21 enhances cardiac fibrotic remodelling and fibroblast proliferation via targeting CADM1. Yuan et al found that miR‐21 promoted cardiac fibrosis after MI via targeting Smad7. In addition, plasma miR‐21 level was significantly higher in patients with acute MI compared with control, suggesting that plasma miR‐21 may be a novel biomarker for acute MI .…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al reported that tumour suppressor cell adhesion molecule 1 (CADM1) is the potential target of miR‐21 and miR‐21 enhances cardiac fibrotic remodelling and fibroblast proliferation via targeting CADM1. Yuan et al found that miR‐21 promoted cardiac fibrosis after MI via targeting Smad7. In addition, plasma miR‐21 level was significantly higher in patients with acute MI compared with control, suggesting that plasma miR‐21 may be a novel biomarker for acute MI .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, increasing evidence supported Smad-7 as the target of microRNA-21 (MiR-21), and MiR-21 binds to 3′ terminus of Smad-7 and then represses the expression of Smad-7, contributing to cardiac fibrosis. 28,29 Because MiR-21 was negatively regulated by PPAR-γ, 30…”
Section: Cyp2j2/eet Inhibits Atrial Fibrosis and Atrial Fibroblast mentioning
confidence: 99%
“…[9][10][11] In brief, rats were anesthetized by intraperitoneal injection of 2% pentobarbital sodium (2 mL/kg) for left thoracotomy and pericardiotomy. [9][10][11] In brief, rats were anesthetized by intraperitoneal injection of 2% pentobarbital sodium (2 mL/kg) for left thoracotomy and pericardiotomy.…”
Section: Modelmentioning
confidence: 99%